Estimation of some genetic parameters, correlation and path coefficient analysis for Faba bean varities under two plant densities. - Hadi, Banan hassan; Hassan, W. .A; Mohamed, F. F.; Kathem, Z. K. (Journal of Kerbala for Agricultural Sciences, 2018)
The experiment was carried out during the season 2016-2017 in Al-Dora/Al-Buetha village, using Randomized Complete Block Design (RCBD)with three replications by factorial experiment arrangement . The experiment included two factors, the first: varieties (Turki, Ukrani, Spanish, Syrian, Duth, and local).The second factor: plant densities (47.62, 71.34 thousands plant.hectar-1). Genotypic, phenotypic variation, heritability, co-heritability, correlation coefficient and path analysis was estimated for each density for nine traits: plant height, numbet. of branches.plant-1, no. of leaves plant-1, total dry matter, number of pods.plant-1 , pods weight, number. of seeds.pod-1 , pod length and seed yield.plant-1.The results showed high significant different for all studied traits for both densities. There was a high genetic variation for no. of leaves.plant-1, plant height and total dry matter, that reached (249.91, 129.52, and 116.65)respectively in the first density and (327.58, 110,292.01) for second density. The higher value of heritability broad sense appeared in plant height, number of leaves and pod length in first density, for plant height, number of leaves and total dry matter in second density. The higher value of co-heritability appeared between no. of branches.plant-1 and number. of pods.plant-1 and between number of pods.plant-1 and pod weight that reached 1.825and 1.838 in first density .Co-heritability between number of branches plant-1, no. of pods.plant-1 and no. of seeds.pod-1 that reached 1.355 and 1.149 in second density. Genotypic correlation coefficient higher than phenotypic coefficient, this indicates that gene action leads the main role in these traits that plant breeder can rely on the selection genotypes of high production from the faba bean. The higher genetic, phenotypic correlations were for number of leaves and total dry matter with seed yield in first density, and pods weight, total dry matter with seed yield in second density. The path coefficient analysis results showed that the pod weight.plant-1 and pod length had a higher direct effect in first density and for total dry matter and no. of seeds.pod-1 in second density, and thus, these traits can be used as selection criteria under the studied densities for selection of high yield.